PELATIHAN CARA PRODUKSI DAN REGISTRASI MAKANAN YANG BAIK, AMAN DAN HALAL BAGI MASYARAKAT KHALAYAK SMK NEGERI 4 BOJONEGORO - isnaeni isnaeni isnaeni; Suko Hardjono Suko Hardjono Suko Hardjono; Asri Darmawati Asri Darmawati Asri Darmawati; Noor Erma Nasution Noor Erma Nasution Sugijanto; Juni Ekowati Juni Ekowati Juni Ekowati; Sugijanto Sugijanto Randiman; Muhammad Yuwono Muhammad Yuwono Muhammad yuwono (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2020)
Community Service Activities (PENMAS) were held in August 2018 in Kapas, Bojonegoro with a target audience of SMKN 4 communities, totaling 107 people, consisting of students majoring in Cooking, members of Dharma Wanita, Chefs from 2hotels, several UMKM Food and Beverages around the school, teachers and partisipants from other schools. The activity was also attended by the Principal, the Head of the Education Office who witnessed the signing of the MOU between the PENMAS Team and the school. One of the Departments managed by SMK 4 is Tata Boga with thelearning outcome to prepare entrepreneurs or businessmen of food products. As a vocational school that has held the ISO 9001 2008 certificate, the school is obliged to prepare graduates according to the demands of their competence. Based on preliminary studies, information was obtained that there were several problems related to food consumption and production and government regulationin the case of traded food businesses. The training materials provided in this training were: Food business production regulation (1), How to make good food (2),Ingredients additional allowable food (3), Prohibited food additives and substitute alternatives (4), Good packaging methods and techniques for food and beverage (5), Halal Assurance System (SJH) and Halal food product Certification Process (6) and Simple marketing for food business (7). Based on the evaluation of the pre-test and post-test resulted that after the training participants' understanding showed an increasing trend. Three topics that showed a significant increase in understanding were: Requirements for clean and healthy food (1), Introduction of food coloring logos (2), and Examples of halal food ingredients (3). PENMAS activities will be followed up with intensive coaching activities for students of SMKN4 which are included in the group of beginner beverage food businesses.